2016
DOI: 10.1371/journal.pone.0153761
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis and Epidemic History of Hepatitis C Virus Genotype 2 in Tunisia, North Africa

Abstract: HCV genotype 2 (HCV-2) has a worldwide distribution with prevalence rates that vary from country to country. High genetic diversity and long-term endemicity were suggested in West African countries. A global dispersal of HCV-2 would have occurred during the 20th century, especially in European countries. In Tunisia, genotype 2 was the second prevalent genotype after genotype 1 and most isolates belong to subtypes 2c and 2k. In this study, phylogenetic analyses based on the NS5B genomic sequences of 113 Tunisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Combination of Elbasvir (NS5A inhibitor) and Grazoprevir (NS3/4A protease inhibitor) for treating genotypes 1 and 4 produced high SVR rates [23] . HCV genotyping is clinically important in predicting the efficiency of antiviral therapy, in determining the duration of treatment [24] and, also, in detecting HCV molecular epidemiology [25] . This study aims to genotype HCV strains circulating in Damietta Governorate and to investigate the variation in HCV NS5B region that is targeted by the newly approved antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of Elbasvir (NS5A inhibitor) and Grazoprevir (NS3/4A protease inhibitor) for treating genotypes 1 and 4 produced high SVR rates [23] . HCV genotyping is clinically important in predicting the efficiency of antiviral therapy, in determining the duration of treatment [24] and, also, in detecting HCV molecular epidemiology [25] . This study aims to genotype HCV strains circulating in Damietta Governorate and to investigate the variation in HCV NS5B region that is targeted by the newly approved antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 15 subtypes have been confirmed for GT‐2 (2a‐2u), with frequencies varying among countries . The spread of GT‐2 is thought to have started at the beginning of the 20th century due to slave trade . GTs 2a, 2b, and 2c have been identified worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found two patients (4%) had GT‐2j and one (2%) had a mixed infection with GT‐2k + 2j. We believe that European populations migrating to the Americas may have helped spread GT‐2j …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype 1 is the most common, especially subtype 1b, with prevalence of around 80% followed by genotype 2 with prevalence of 10% approximatively [ 12 14 ]. HCV genotype 2 has been poorly studied in Tunisia and until now only two studies have investigated its genetic diversity and molecular epidemiology [ 15 , 16 ]. The study conducted in 2014 showed that the major circulating subtype is subtype 2c (75.5%).…”
Section: Introductionmentioning
confidence: 99%